Chlorophylls derivatives: Photophysical properties, assemblies, nanostructures and biomedical applications. (May 2021) - Cai, Jun-Quan; Liu, Xiu-Mei; Gao, Zi-Jun; Li, Li-Li; Wang, Hao
Graphical abstract: In this review, we focus on the following points: classifications of chlorophyll based on chemical structure, and its relationship with photophysical properties; biomedical-explored chemical modification of chlorophylls to control the molecular stacking; supramolecular structures, dynamic assembly or transformation in physiological condition; visual characterization of nanostructures and quantitative analysis of in situ assembly; biomedical utility based on assembly enhanced photoacoustic, fluorescence, PET, MRI and multimode imaging, as well as improved photodynamic, photothermal therapy. Abstract: Chlorophylls are one of the most abundant organic pigments on the earth, which play an important role in the photosynthesis of plants, algae and bacteria. With the development of chromatography and chemical synthesis technology, many new chlorophylls from nature have been identified, and similar typical heterocyclic macrocyclic chlorophyll derivatives have also been designed and synthesized. Their chemical structures have significantly affected the absorption of light, energy transfer efficiency, excited-state lifetime, etc. Inspired by the chlorophylls interactions in chloroplasts for light-harvesting, we realized that intramolecular assembly and the resultant nanostructures played a more prominent role in their photophysical and photochemical properties, even in further biomedical applications, such as photodynamic and photothermal therapy, photocatalytic diagnosis, as well as optical, photoacoustic, magnetic resonance and nuclear medical imaging. In this review, we discuss the photo-properties of chlorophylls, overview the driving forces of assembly, and summarize biomedical-relevant advantages incorporated supramolecular nanostructures. In particular, the dynamic assembly under physiological condition provides unpredictable and interesting biological effects, such as aggregation/assembly induced drug retention in disease areas, optimized biodistribution and optimized the pharmacokinetics. The labeling on the assembly also provides a useful tool for us to observe the self-assembled nanostructures in vivo in a non-invasive way. Through the elaboration of different examples of chlorophylls, we hope to provide some inspiration for the biomedical application design of chlorophylls derivatives.